Relationship between muscular impairment and psychological health with lower extremity functions in patients with transtibial amputation - Ayesha Aslam; Harima Shoukat; Jahan, Saira (Journal of the Pakistan Medical Association, 2022)
Objectives: To determine the relationship of muscular impairment and psychological health with lower extremity functions in patients with transtibial amputation. Method: The correlational study was conducted from March to September 2021 at the Fauji Foundation Hospital, Rawalpindi, Pakistan, and comprised male patients with transtibial amputation. Data was collected using the depression anxiety stress scale and the lower extremity functional scale. The correlation of muscular impairment and psychological health with lower extremity functions was determined. Data was analysed using SPSS 21. Results: There were 85 male patients with a mean age of 53.74+11.30 years. There was weak iliopsoas muscle strength 4.64+0.50 and reduced muscle length of hamstrings 67.00+6.41 on the affected side. There was non-significant correlation in muscle atrophy of both amputated limb (p=0.82) and non-amputated limb (p=0.58) with lower extremity function. Significant inverse correlation was present between depression, anxiety and stress (p=0.001) with lower extremity function. Conclusion: Weak iliopsoas muscle strength and tight hamstrings were observed on the amputated side. Muscle atrophy was more in non-amputated limb than amputated limb. There was significant inverse correlation of depression, anxiety and stress with lower extremity function. Key Words: Anxiety, Depression, Muscle atrophy, Muscle length, Muscle strength, Stress.